Presentation: Cusco, chronicles of the end of the century - Glave, Luis Miguel (1991)
To close this Allpanchis series dedicated to the V Centenary and the Andean territories, this monographic issue of the magazine brings together works on Cusco and its region. Few cities in the world and in history can exhibit the magical halo that this ancient Andean center has, with an eternal name in words and memory, even though it changes letters in its writing. All Peruvians and people from the Andes and all those who are interested in our destinations will agree that, for different reasons, Cusco has been and is a symbol of ourselves.